The Effects of Peer Presence on Variables Maintaining Moderate-to-Vigorous Physical Activity in Children. Issue 6 (November 2020) - Gonzales, Tiffany; Jackson, Marianne L.; Nicolson, Amanda
An increasing number of children fail to meet the recommended levels of physical activity. The purpose of this study was to examine the effects of peer presence on variables that have been shown to evoke moderate-to-vigorous physical activity (MVPA) in children. We recorded the levels of MVPA in three preschool children across no adult, attention, and interactive play conditions, with a peer present and absent. All conditions were compared with a naturalistic baseline and presented in a multielement design with a brief reversal to baseline and reintroduction of the most effective condition. All three participants displayed most MVPA during the interactive play condition with a peer present. This study furthers research on the identification of variables that evoke MVPA in young children and emphasizes the interaction of peer presence and contingent social positive reinforcement as relevant variables.